Konsep Zalim dalam Al-Qu’ran Tinjauan Pemikiran Tan Malaka (Jurnal Studi Al-Qur'an, 2023)
Tyranny is a sin that has been explained in detail in the Qur'an. The form of tyranny today is still often developing in people's lives. This study aims to elaborate on Tan Malaka's thoughts regarding tyranny. This study uses a qualitative approach using library research and data collection techniques using documentation. The analysis technique used the descriptive-analysis method and then studied and connected with the character's thoughts, Tan Malaka. The results showed that Tan Malaka saw three forms of tyranny. 1) Every individual who did not get a decent job and did not get fair wages, 2) Did not get proper education, 3) Oppression of fellow human beings. According to Tan Malaka, the way to overcome this is through education: 1) providing sufficient weapons for the needs of life in the world of capital, 2) giving rights to students by way of association, and 3) showing obligations towards the kromo.